MiR-124-3p mediates gastric cancer cell ferroptosis induced by an anti-cancer drug polyphyllin I - Zheng, Fang; Bi, Jian-Can; Wei, Yu-Yan; Wang, Yeshu; Zhang, Qunfang; Liang, Chun-Ling; Wu, Jianwei; Dai, Zhenhua (Frontiers in Pharmacology, 2023)
Ferroptosis is an emerging type of regulated cell death and associated with antitumoral therapy, while some microRNAs have been shown to regulate the tumorigenesis and cancer progression. Meanwhile, polyphyllin I (PPI) has exhibited antitumoral effects by promoting cancer cell apoptosis and ferroptosis. However, it is unclear whether PPI induces cancer cell ferroptosis by regulating microRNAs.We used two gastric cancer cell lines (AGS and MKN-45) to set up a tumor model of the nude mice, which were then treated daily with PPI to measure the cancer growth in vitro and in vivo. Ferroptosis was measured using immunofluorescence staining and flow cytometric analysis according to levels of intracellular ROS, lipid ROS and ferrous ions. Moreover, NRF2 expression was measured by Western blotting. In some experiments, the mimics or inhibitors of miR-124-3p were used to further confirm its involvement in PPI-induced cancer cell ferroptosis.Here we found that miR-124-3p mediated cancer ferroptosis and tumor repression induced by PPI since PPI increased miR-124-3p expression in gastric cancer cells and promoted their ferroptosis, whereas inhibition of miR-124-3p mostly abolished the effects of PPI on tumor growth, ferroptosis and NRF2 expression. Moreover, miR-124-3p mimics promoted cancer 3 cell ferroptosis by downregulating NRF2 through directly targeting 3'-UTR region of NRF2, confirming a role for miR-124-3p in regulating PPI-induced ferroptosis.PPI exerts its antitumoral effects on the gastric cancer by promoting cell ferroptosis via regulating miR-124-3p. Our findings have clinical implications for cancer chemotherapy.